2015
DOI: 10.1080/09291016.2015.1020200
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation inin vitroimmune activity of milk leukocytes in elite and non-elite crossbred cows of Indian sub-tropical semi-arid climate

Abstract: Immunity of mammary gland in terms of in vitro activity of milk leukocytes has been evaluated during hot-humid, summer, and winter season in elite (n = 10) and non-elite (n = 10) crossbred cows. Milk samples were collected from all the cows throughout the year at 15-day interval. Milk somatic cell counts (SCC) and differential leukocyte counts (DLC) were evaluated microscopically. Milk neutrophils, macrophages, and lymphocytes were isolated and cultured in vitro. In vitro PI of milk neutrophils and macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…The highest BMSCC around the period of calving was observed in the winter, and the lowest BMSCC in these herds occurred shortly after the calving period [ 49 ]. Higher levels of SCC during hot-humid season in elite cows compared to non-elite cows indicate more stress level on the udder of these animals during this particular season [ 50 ]. In milk, casein (except γ-CN) was lower in the summer and higher during the winter season.…”
Section: Factors Affecting Milk Sccmentioning
confidence: 99%
“…The highest BMSCC around the period of calving was observed in the winter, and the lowest BMSCC in these herds occurred shortly after the calving period [ 49 ]. Higher levels of SCC during hot-humid season in elite cows compared to non-elite cows indicate more stress level on the udder of these animals during this particular season [ 50 ]. In milk, casein (except γ-CN) was lower in the summer and higher during the winter season.…”
Section: Factors Affecting Milk Sccmentioning
confidence: 99%
“…The higher SCCs in milk, the lower the products with a shorter shelf life and vice versa. As the SCC rises, the severity of intramammary infection elevates and leads to a decreased milk yield and quality (Mukherjee et al., 2015 ). levels of SCC during hot‐humid season become higher in elite cows compared to non‐elite cows indicating more stress level on the udder of these animals during this particular season (Mukherjee et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…As the SCC rises, the severity of intramammary infection elevates and leads to a decreased milk yield and quality (Mukherjee et al., 2015 ). levels of SCC during hot‐humid season become higher in elite cows compared to non‐elite cows indicating more stress level on the udder of these animals during this particular season (Mukherjee et al., 2015 ). In milk, casein (except γ‐CN) was lower in the summer and higher during the winter season, whereas immunoglobulin G and serum albumin contents were higher in summer than in winter and spring seasons (Bernabucci et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…High-milk-producing cows experience increased stress due to production demands, compromising their immunity and resulting in elevated SCC in their milk [22]. This effect is especially pronounced in high-producing cows during hot and humid seasons compared to their mid-and low-producing counterparts, indicating increased udder stress during this period [51]. Lee et al [45] reported a significant increase in SCC in cows when the THI exceeded the breakpoint, a finding mirrored by Hagiya et al [52], who observed a marked increase in SCC beyond the THI threshold.…”
Section: Effect Of Temperature-humidity Indexmentioning
confidence: 99%